1998
DOI: 10.1182/blood.v92.8.2815
|View full text |Cite
|
Sign up to set email alerts
|

RP105 Is Associated With MD-1 and Transmits an Activation Signal in Human B Cells

Abstract: RP105 was originally discovered as a mouse B-cell surface molecule that transmits an activation signal. The signal leads to resistance against irradiation-induced apoptosis and massive B-cell proliferation. Recently, we found that mouse RP105 is associated with another molecule, MD-1. We have isolated here the human MD-1 cDNA. We show that human MD-1 is also associated with human RP105 and has an important role in cell surface expression of RP105. We also describe a monoclonal antibody (MoAb) that recognizes h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
64
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(68 citation statements)
references
References 19 publications
3
64
0
1
Order By: Relevance
“…Two other significantly repressed genes are LY64 and LY86. LY64, also known as RP105, was originally cloned as a B‐cell‐specific molecule and is able to drive B‐cell proliferation (Miura et al , 1998). LY64 is a specific homolog of TLR4.…”
Section: Discussionmentioning
confidence: 99%
“…Two other significantly repressed genes are LY64 and LY86. LY64, also known as RP105, was originally cloned as a B‐cell‐specific molecule and is able to drive B‐cell proliferation (Miura et al , 1998). LY64 is a specific homolog of TLR4.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work from this and other laboratories suggested that the molecule MD‐1 was involved in the transmission of activation signals within lymphoid cells (12, 13). The molecule is thought to act by stabilizing expression of cell‐surface coreceptors which transmit signals leading to the activation of nuclear factor‐κB (NF‐κB) in APCs, which in turn can result in enhanced expression of the costimulatory molecules CD80/CD86 (12–15).…”
mentioning
confidence: 85%
“…Previous work from this and other laboratories suggested that the molecule MD‐1 was involved in the transmission of activation signals within lymphoid cells (12, 13). The molecule is thought to act by stabilizing expression of cell‐surface coreceptors which transmit signals leading to the activation of nuclear factor‐κB (NF‐κB) in APCs, which in turn can result in enhanced expression of the costimulatory molecules CD80/CD86 (12–15). We have shown in addition that functional blockade of MD‐1 expression results in decreased expression of these costimulatory molecules, prolongs both allogeneic and xenogeneic skin graft survival in mice, and prevents type‐1 cytokine‐induced fetal loss (12, 14, 16).…”
mentioning
confidence: 85%
“…17). Anti-CD180 antibodies with a stimulatory function (MHR73-11) and without a stimulatory function (N2C1) were obtained from BioLegend and GeneTex, respectively (18,19). LPS, Pam3Csk, flagellin, poke weed mitogen, and SN-50 were dissolved in 0.9% NaCl.…”
Section: Reagentsmentioning
confidence: 99%